2015
DOI: 10.3945/an.114.007914
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Individuals with Autism Spectrum Disorders: Do We Know Enough?

Abstract: The incidence of individuals with autism spectrum disorders (ASDs) is on the rise; therefore, well-timed screening is important. Given that this is a nutritionally vulnerable population, it is imperative to conduct a detailed nutritional assessment so that timely and intensive interventions can be recommended. This review article summarizes the research, focusing on the nutritional status of individuals with ASDs based on their anthropometric measurements, biomarkers, and dietary assessments. Research examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 74 publications
(154 reference statements)
4
85
0
15
Order By: Relevance
“…Although inadequate micronutrient but adequate macronutrient intakes are increasingly reported, there are inconsistent results about the extent and type of nutrient deficiencies (for review see [265]). Micronutrient as essential amino acids, minerals, and vitamins are indispensable for human health, primarily due to their critical function as enzymatic cofactors for numerous reactions in the body, such as the production of neurotransmitters and fatty acid metabolism.…”
Section: Nutritional Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inadequate micronutrient but adequate macronutrient intakes are increasingly reported, there are inconsistent results about the extent and type of nutrient deficiencies (for review see [265]). Micronutrient as essential amino acids, minerals, and vitamins are indispensable for human health, primarily due to their critical function as enzymatic cofactors for numerous reactions in the body, such as the production of neurotransmitters and fatty acid metabolism.…”
Section: Nutritional Statusmentioning
confidence: 99%
“…The prevalence of iron deficiency and anemia in subjects with autism is reported between 24 and 32% and 8 and 16%, respectively. Because iron deficiency, with or without anemia, results in impaired cognition and developmental defects, iron deficiency in children with autism could further compromise their communication and behavioral impairments [265]. Thus, ferritin levels should be measured in subjects with autism as a part of routine investigation [275].…”
Section: Mineralsmentioning
confidence: 99%
“…3,6 The mothers' narratives reflect these difficulties that are intrinsic to ASD; however, they also indicate that these characteristics may not be determinant when adequate environmental stimulus successfully results in the introduction of new eating habits.…”
Section: Food-related Behaviormentioning
confidence: 99%
“…Some authors have suggested that children with autism tend to restrict their diet to an extremely narrow range of foods, with associated food neophobia and sensory problems. 3 Furthermore, sensory factors such as smell, texture, color and temperature may contribute to this behavior. [4][5][6] A literature review of seven descriptive studies found the prevalence of eating problems in children with ASD to range between 46 and 89% in the patients evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Further, inadequate micronutrient-but adequate macronutrient-intakes are increasingly reported. Thus, several lines of evidence implied that patients with ASD disorders are likely to display dysregulated amino acid metabolism, increased concentrations of homocysteine, and/or decreased levels of the vitamins folate, B-6, B-12 and vitamin-D, thereby suggesting possible biomarkers for an early diagnosis of ASDs [22]. Other studies have reported that supplemental nutrients such as omega-3 fatty acids, zinc, magnesium, and some phytochemicals may evoke moderate benefits, while avoidance of food allergens, chemicals, and chelation therapy can afford some aid to autism patients.…”
Section: Epigenetic Modifications and Interplay With Environmental Famentioning
confidence: 99%